Pengaruh Pelatihan Hijau dan Perilaku Berwawasan Lingkungan terhadap Manajemen Rantai Pasok Hijau Menuju Industri Kelapa Sawit yang Berkelanjutan (Studi Kasus Petani Kelapa Sawit di Kabupaten Musi Banyuasin, Sumatera Selatan) - Henny Hendarjanti; Heri DB; Lenny Christina Nawangsari (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2023)
Hendarjanti H, DB Heri, Nawangsari LC. 2022. Impact green training and environmentally friendly behavior to green supply chain management towards sustainable palm oil industry (case study on oil palm farmer in Musi Banyuasin, South Sumatera). In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 885-897. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Oil palm smallholders have an important role in ensuring the supply of Indonesian crude palm oil. They must increase their production capacity and product quality of palm oil raw materials. Farmers need to make changes so that they can produce quality palm oil. Also, oil palm smallholders need to form a business entity to have strength and selling points in the palm oil processing industry. Farmers are the main actors involved in crude palm oil's environmentally friendly supply chain. This study aimed to examine the impact of green training and environmentally sound behaviour on the availability of green supply chains in a sustainable palm oil industry. This study uses quantitative methods through data collection using questionnaire sheets to 82 oil palm farmers who participated in Oil Palm Cultivation Technical Training in Palembang organized by Badan Pengelola Dana Perkebunan Kelapa Sawit (BPDPKS), Direktorat Jenderal Perkebunan and Best Planter Indonesia (BPI). Data were analyzed using partial least squares structural equation modelling software (Smart PLS 3.3.3). The results show that Green Training and Environmentally Friendly Behavior significantly affect Green Supply Chain Management. Green Training implemented in Green Insight Behavior will encourage farmers to take initiatives and take environmentally friendly actions to minimize the impact on the environment. Environmentally Friendly Behavior positively affects Green Supply Chain Management, especially on Integrated Pest Management. This study develops a comprehensive empirical model that examines the co-effect of Green Training and Farmer Environmentally Friendly Behavior in achieving a sustainable oil palm agribusiness industry.